Inter-laboratory comparison on the size and stability of monodisperse and bimodal synthetic reference particles for standardization of extracellular vesicle measurements. (4th February 2016) - Nicolet, Anaïs; Meli, Felix; van der Pol, Edwin; Yuana, Yuana; Gollwitzer, Christian; Krumrey, Michael; Cizmar, Petr; Buhr, Egbert; Pétry, Jasmine; Sebaihi, Noham; de Boeck, Bert; Fokkema, Vincent; et al.
Abstract: In future, measurements of extracellular vesicles in body fluids could become a standard diagnostic tool in medicine. For this purpose, reliable and traceable methods, which can be easily applied in hospitals, have to be established. Within the European Metrological Research Project (EMRP) 'Metrological characterization of micro-vesicles from body fluids as non-invasive diagnostic biomarkers' (www.metves.eu ), various nanoparticle reference materials were developed and characterized. We present results of an international comparison among four national metrology institutes and a university hospital. The size distributions of five monodisperse and two bimodal spherical particle samples with diameters ranging from 50 nm to 315 nm made out of silica and polystyrene were compared. Furthermore, the stability of the samples was verified over a period of 18 months. While monodisperse reference particle samples above a certain size level lead to good agreements of the size measurements among the different methods, small and bimodal samples show the limitations of current 'clinical' methods. All samples proved to be stable within the uncertainty of the applied methods.